Isolation of endophytic fungi from benalu batu (Begonia medicinalis) and their toxicity on Artemia Salina - Syariful Anam; Armini Syamsidi; Musyahidah Musyahidah; Nurul Ambianti; Agustinus Widodo; Muhammad Sulaiman Zubair (Jurnal Ilmiah Farmasi, 2022)
Abstract   Background: Endophytic fungi are microorganisms found in plant tissues that are mutually beneficial to the host plant. They are known as sources of bioactive metabolites which possess various biological activities such as antimicrobial, anticancer, antiviral, antifungal, and antioxidant.  Benalu batu (Begonia medicinalis) has been used empirically as a medicinal plant and has shown anticancer activity in breast cancer cells (T47D cells) and cervical cancer cells (HeLa cells).Objective: This study aimed to isolate the endophytic fungi from benalu batu and determine the toxicity activity and Lethal Concentration 50% (LC50) value of isolated endophytic fungi using shrimp larvae (Artemia salina). Method: Endophytic fungi were isolated from fresh parts; leaves, stems, roots of Benalu Batu. The selected parts were sterilized with ethanol 70% and sodium hypochlorite 1% subsequently placed into Potato Dextrose Agar Chloramphenicol (PDAC) then incubated at 28°C for 7 days. Isolated endophytic fungi were extracted by sonication method using ethyl acetate. The toxicity activity of isolated endophytic fungi was determined using the Brine Shrimp Lethality Test (BSLT).Results: Isolation of the endophytic fungi from benalu batu obtained 10 isolates, which the leaves part obtained 6 isolates, the stem obtained 3 isolates and the root obtained 1 isolate. The results of screening for toxicity test of 10 isolates at concentrations of 500 µg/mL shown that isolate D3, D5, and D6 gave 100% mortality. The LC50 values of isolate D3, D5, and D6 were obtained respectively in 448.03, 8.784, and 9.13 µg/mL.Conclusion: These results indicated that isolate D5 exhibits the greatest toxicity and needs to be investigated the activity for testing on cancer cells.Keywords: endophytic fungi, Begonia medicinalis, toxicity, Artemia salina Intisari  Latar belakang: Jamur endofit merupakan mikroorganisme yang terdapat dalam jaringan tumbuhan yang bersifat mutualisme terhadap tumbuhan inang. Jamur endofit telah diketahui sebagai sumber metabolit yang memiliki beberapa aktivitas biologi seperti antimikroba, antikanker, antivirus, antijamur, dan antioksidan. Tumbuhan benalu batu (B. medicinalis) telah digunakan secara empiris dan terbukti memiliki aktivitas antikanker pada sel kanker payudara (Sel T47D) dan sel kanker leher rahim (Sel HeLa). Tujuan: Studi ini bertujuan untuk melakukan isolasi jamur endofit dari benalu batu dan mengetahui toksisitas isolat jamur endofit serta menentukan nilai Lethal Concentration 50% (LC50) terhadap larva udang (Artemia salina)Metode: Jamur endofit diisolasi dari bagian segar; daun, batang, akar benalu batu. Bagian-bagian tersebut disterilisasi dengan etanol 70% dan natrium hipoklorit 1% selanjutnya diletakkan pada media Potato Dextrose Agar Chloramphenicol (PDAC) kemudian diinkubasi pada suhu 28°C selama 7 hari. Isolat jamur endofit diekstraksi dengan metode sonikasi menggunakan etil asetat. Aktivitas toksisitas isolat jamur endofit ditentukan menggunakan metode Brine Shrimp Lethality Test (BSLT).Hasil: Isolasi jamur endofit dari benalu batu diperoleh 10 isolat, bagian daun diperoleh 6 isolat, bagian batang diperoleh 3 isolat dan bagian akar diperoleh 1 isolat. Hasil penapisan uji toksisitas 10 isolat pada konsentrasi 500 µg/mL menunjukkan bahwa isolat D3, D5, dan D6 memberikan persentase mortalitas sebesar 100%. Nilai LC50 isolat D3, D5, dan D6 diperoleh masing-masing sebesar 448,03, 8,784, dan 9,13 µg/mL.Kesimpulan: Hasil ini menunjukkan isolat D5 memiliki toksisitas paling besar dan perlu dilanjutkan untuk pengujian pada sel kanker.Kata kunci : jamur endofit, Begonia medicinalis, toksisitas, Artemia salina